Educational intervention does not reduce non‐invasive urine contamination rates in children presenting to the emergency department. (19th June 2019) - Jacob, Ron; John‐Denny, Blessy; Donaldson, Katherine; White, Brent; Outhred, Alexander; McCaskill, Mary E
Abstract : Aim: Urinary tract infection is common in children with high contamination rates with non‐invasive urine sampling (NIU). Our aims were to evaluate an educational tool for decreasing contamination rates and find factors associated with contamination. Methods: This was a prospective cohort interventional study with a review of microbiology data and medical records of all NIU specimens collected at a large tertiary children's emergency department (ED) over a 1‐year period. The intervention was the provision of a urine collection kit and educational pamphlet and education of staff. NIU contamination was calculated for 6 months pre‐intervention and 6 months post‐intervention. The association of factors with NIU contamination was evaluated for all cohorts (age, gender, presence of diarrhoea, season, time of day, time to incubation and activity of the ED). Results: A total of 2104 NIU samples were included (median age 3 years, 52% females). There was no difference between periods in contamination rates (29.2% and 31.2%, respectively, P = 0.322). Collectively, high monthly activity of the department, age and female gender were associated with contamination. The highest contamination rates were among children aged 0–3 months and 12 years and older (38.1 and 48.9%, respectively). Conclusions: The urine collection kit and educational tool did not decrease NIU contamination rates in our ED. Contamination rates were correlated with the monthly activity of our department and female gender and were noticeably high among infants and adolescents. Given the high prevalence of urinary tract infection among these age groups, measures should be taken to reassess indications and methods for urine collection.